Large-scale synthesis of a monophosphonated tetrathiatriarylmethyl spin probe for concurrent in vivo measurement of pO2, pH and inorganic phosphate by EPR. Issue 42 (27th July 2021) - Gluth, Teresa D.; Poncelet, Martin; DeVience, Stephen; Gencheva, Marieta; Hoblitzell, Emily. H.; Khramtsov, Valery V.; Eubank, Timothy D.; Driesschaert, Benoit
Abstract : We report a new strategy for the synthesis of a mono-phosphonated triarylmethyl radical spin probe and a standalone application with a user-friendly interface for automatic spectrum fitting and extraction of p O2, pH, and [Pi ] values. Abstract : Low-field electron paramagnetic resonance spectroscopy paired with pTAM, a mono-phosphonated triarylmethyl radical, is an unmatched technique for concurrent and non-invasive measurement of oxygen concentration, pH, and inorganic phosphate concentration for in vivo investigations. However, the prior reported synthesis is limited by its low yield and poor scalability, making wide-spread application of pTAM unfeasible. Here, we report a new strategy for the synthesis of pTAM with significantly greater yields demonstrated on a large scale. We also present a standalone application with user-friendly interface for automatic spectrum fitting and extraction of p O2, pH, and [Pi ] values. Finally, we confirm that pTAM remains in the extracellular space and has low cytotoxicity appropriate for local injection.